Activation of Natural Killer Cells by Newcastle Disease Virus Hemagglutinin-Neuraminidase - Jarahian, Mostafa (American Society for Microbiology (ASM), 2009)
The avian paramyxovirus Newcastle disease virus (NDV) selectively replicates in tumor cells and is known to stimulate T-cell-, macrophage-, and NK cell-mediated responses. The mechanisms of NK cell activation by NDV are poorly understood so far. We studied the expression of ligand structures for activating NK cell receptors on NDV-infected tumor cells. Upon infection with the nonlytic NDV strain Ulster and the lytic strain MTH-68/H, human carcinoma and melanoma cells showed enhanced expression of ligands for the natural cytotoxicity receptors NKp44 and NKp46, but not NKp30. Ligands for the activating receptor NKG2D were partially downregulated. Soluble NKp44-Fc and NKp46-Fc, but not NKp30-Fc, chimeric proteins bound specifically to NDV-infected tumor cells and to NDV particle-coated plates. Hemagglutinin-neuraminidase (HN) of the virus serves as a ligand structure for NKp44 and NKp46, as indicated by the blockade of binding to NDV-infected cells and viral particles in the presence of anti-HN antibodies and by binding to cells transfected with HN cDNA. Consistent with the recognition of sialic acid moieties by the viral lectin HN, the binding of NKp44-Fc and NKp46-Fc was lost after desialylation. NKp44- and NKp46-CD3ζ lacZ-inducible reporter cells were activated by NDV-infected cells. NDV-infected tumor cells stimulated NK cells to produce increased amounts of the effector lymphokines gamma interferon and tumor necrosis factor alpha. Primary NK cells and the NK line NK-92 lysed NDV-infected tumor cells with enhanced efficiency, an effect that was eliminated by the treatment of target cells with the neuraminidase inhibitor Neu5Ac2en. These results suggest that direct activation of NK cells contributes to the antitumor effects of NDV.